Undisturbed climbing fiber pruning in the cerebellar cortex of CX3CR1‐deficient mice. Issue 11 (2nd June 2020) - Kaiser, Nicole; Pätz, Christina; Brachtendorf, Simone; Eilers, Jens; Bechmann, Ingo
Abstract: Pruning, the elimination of excess synapses is a phenomenon of fundamental importance for correct wiring of the central nervous system. The establishment of the cerebellar climbing fiber (CF)‐to‐Purkinje cell (PC) synapse provides a suitable model to study pruning and pruning‐relevant processes during early postnatal development. Until now, the role of microglia in pruning remains under intense investigation. Here, we analyzed migration of microglia into the cerebellar cortex during early postnatal development and their possible contribution to the elimination of CF‐to‐PC synapses. Microglia enrich in the PC layer at pruning‐relevant time points giving rise to the possibility that microglia are actively involved in synaptic pruning. We investigated the contribution of microglial fractalkine (CX3 CR1) signaling during postnatal development using genetic ablation of the CX3 CR1 receptor and an in‐depth histological analysis of the cerebellar cortex. We found an aberrant migration of microglia into the granule and the molecular layer. By electrophysiological analysis, we show that defective fractalkine signaling and the associated migration deficits neither affect the pruning of excess CFs nor the development of functional parallel fiber and inhibitory synapses with PCs. These findings indicate that CX3 CR1 signaling is not mandatory for correct cerebellar circuit formation. Main Points: Ablation of CX3 CR1 results in a transient migration defect in cerebellar microglia. CX3 CR1 is not required for functional pruning of cerebellar climbing fibers. Functional inhibitory and parallel fiber synapse development with Purkinje cells is undisturbed in CX3 CR1‐deficient mice. Main Points: Ablation of CX3 CR1 results in a transient migration defect in cerebellar microglia. CX3 CR1 is not required for functional pruning of cerebellar climbing fibers. Functional inhibitory and parallel fiber synapse development with Purkinje cells is undisturbed in CX3 CR1‐deficient mice.